Parents' responses to prognostic disclosure at diagnosis of a child with a high‐risk brain tumor: Analysis of clinician‐parent interactions and implications for clinical practice. Issue 3 (23rd November 2020) - Bluebond‐Langner, Myra; Hall, Nicolas; Vincent, Katherine; Henderson, Ellen M.; Russell, Jessica; Beecham, Emma; Bryan, Gemma; Gains, Jennifer E.; Gaze, Mark N.; Slater, Olga; Langner, Richard W.; Hargrave, Darren
Abstract: Background: Previous studies have found that parents of children with cancer desire more prognostic information than is often given even when prognosis is poor. We explored in audio‐recorded consultations the kinds of information they seek. Methods: Ethnographic study including observation and audio recording of consultations at diagnosis. Consultations were transcribed and analyzed using an interactionist perspective including tools drawn from conversation and discourse analysis. Results: Enrolled 21 parents and 12 clinicians in 13 cases of children diagnosed with a high‐risk brain tumor (HRBT) over 20 months at a tertiary pediatric oncology center. Clinicians presented prognostic information in all cases. Through their questions, parents revealed what further information they desired. Clinicians made clear that no one could be absolutely certain what the future held for an individual child. Explicit communication about prognosis did not satisfy parents' desire for information about their own child. Parents tried to personalize prognostic information and to apply it to their own situation. Parents moved beyond prognostic information presented and drew conclusions, which could change over time. Parents who were present in the same consultations could form different views of their child's prognosis. Conclusion: Population level prognostic information left parents uncertain about their child's future. The need parents revealed was not for more such information but rather how to use the information given and how to apply it to their child in the face of such uncertainty. Further research is needed on how best to help parents deal with uncertainty and make prognostic information actionable.